PELATIHAN PEMASARAN BERBASIS ONLINE DAN MEDIA SOSIAL KEPADA STAFF KELURAHAN JABUNGAN KECAMATAN BANYUMANIK KOTA SEMARANG PROVINSI JAWA TENGAH - Sukma Nur Ardini; Sewandi Suwandi; A. B. Prabowo K. A. Prabowo K. A.; Siti Lestari; M.F Dharmaputra (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2021)
The results of the survey conducted by a team of Universitas PGRI Semarang in January 2018 showed that Kelurahan JabunganSemarang has abundant local potential that is (1) designated as empon-empon thematic village, (2) has a tourist attraction of Bukit Panji Laras, (3) ) has the potential of processed food products, but the problem of this village is the less awareness of the local government and the society. They do not realize the potential of their village needs to be known by the public. Therefore, the team Universitas PGRI Semarang provides solutions through community service programs, especially those related to online-based marketing and social media by applying methods of problem identification, training program, mentoring program, and monitoring and evaluation program. The keynote speaker of this program is Mr. Andi Priyolistiyono, S. Kom, M.Kom, an online marketing expert who collaborates with the team who are also expert and successful business men. The focus of this program is on-line marketing and social media for food products that are made by the local society in Kelurahan Jabungan. The team facilitates this training with producers who have market shares, one of which is Madhang.id. The training results show that the participants are able to master the training materials very well. It is evident by their products have been display at Madhang.id.